PENGARUH PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSET PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN DAGANG MASRI M. SYARIAH CABANG PADANG PERIODE 2008-2012) - Suryadi, Suryadi; Taqwa, Salma; i Areva, Des (Pendidikan Ekonomi, 2014)
ABSTRACTÂ SURYADI (NIM : 09,090,075), Effect Working Capital Turnover Of Return On Assets Company (Case Study of Islamic Trading Company Masri M. Branch Padang Year 2008-2012)Â This study aims to determine the profitability of the company by analyzing the Working Capital Turnover, to determine the level of profitability is pernulis using Return on Assets (ROA) as a measuring tool. The problems that I researched is the influence of the Working Capital Turnover consists of assuming independent variable (Turnover Cash, and Accounts Receivable Turnover Inventory Turnover) in influencing the dependent variable is ROA Masri M. Trading Company Sharia Branch Padang. The method in this research is descriptive quantitative research methods and types of secondary data from the Companys financial statements. Field study data collection techniques followed by observation with the method of data analysis using inductive analysis (classical assumption test), multiple linear regression analysis, the coefficient of determination, t test and f test. Based on the statistical analysis of the coefficient of determination there is a strong influence of the Working Capital Turnover on ROA at 91.30 % value of the remaining 8.70 % is influenced by other factors. hypothesis t test results showed Working Capital Turnover value t_hitung > t_tabel and f test showed the value F_hitung > F_tabel . Therefore, the Working Capital ought always be taken by the company.